(untitled) (MMIT Proceedings, 2025)
This article reveals the idea of school as a space where a humane personality is formed. It considers the concept of school not only as an educational institution, but also as a workshop where human qualities such as respect, kindness, responsibility and empathy are nurtured. Special attention is paid to the role of the teacher as a mentor and carrier of humanistic values, as well as to the conditions under which it is possible to create an emotionally safe, supportive and developing environment.